2013
DOI: 10.1152/ajplung.00419.2012
|View full text |Cite
|
Sign up to set email alerts
|

LPS induces pp60c-src-mediated tyrosine phosphorylation of Hsp90 in lung vascular endothelial cells and mouse lung

Abstract: Heat shock protein 90 (Hsp90) inhibitors were initially developed as anticancer agents; however, it is becoming increasing clear that they also possess potent anti-inflammatory properties. Posttranslational modifications of Hsp90 have been reported in tumors and have been hypothesized to affect client protein- and inhibitor-binding activities. In the present study we investigated the posttranslational modification of Hsp90 in inflammation. LPS, a prototypical inflammatory agent, induced concentration- and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 51 publications
(47 reference statements)
1
37
0
Order By: Relevance
“…Western blot analyses and immunoprecipitation experiments were performed as described previously (9,31). Densitometry was performed using Image Studio version 3.1 from Licor and plotted as fold change from vehicle.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blot analyses and immunoprecipitation experiments were performed as described previously (9,31). Densitometry was performed using Image Studio version 3.1 from Licor and plotted as fold change from vehicle.…”
Section: Methodsmentioning
confidence: 99%
“…Src -dependent Y-300 phosphorylation of Hsp90 (9). Inhibitors of Hsp90 block LPS-induced Y-300 phosphorylation in cultured human lung microvascular endothelial cells (HLM-VEC) (9) and prolong survival, attenuate inflammation, and reduce lung injury in a murine model of LPS-induced ALI/ ARDS (15).…”
Section: Lps Potentiates Hsp90 Chaperone Function By Inducing Pp60mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitors of Hsp90 also prevented LPS-induced lung endothelial barrier dysfunction by suppressing Src-mediated RhoA activity and signaling (18). In a recent study, Barabutis and coworkers (9) showed that LPS causes phosphorylation of HSP90 on the tyrosine Y309 residue in a Src-dependent manner. Expression of a nonphosphorylatable Hsp90 mutant reduced LPS-induced barrier dysfunction indicating HSP90 inhibition.…”
Section: Endothelial Scaffoldsmentioning
confidence: 96%
“…Although Hsp90 inhibitors were initially developed as antineoplastic drugs, an emerging body of evidence suggests that their anti-inflammatory activity enable them to have a beneficial role in the wider spectrum of human pathology [13][14][15]. We recently remonstrate that p53 is an Hsp90 client protein and that the anti-inflammatory and vascular barrier protective effects of Hsp90 inhibitors are due-at least in part-to p53 mediated actions [16].…”
mentioning
confidence: 99%